Shadow banking, relationship banking, and the economics of depression - Bianco, Antonio (PSL Quarterly Review, 2016)
The paper explores whether a theory of banks doing ‘finance through money creation’ implies a reconsideration of demand-side macro theory as well. To this aim, a simple methodological accounting model of the influence of financial markets over the real economy is presented. The model allows a tidy comparison of relationship and shadow banking, interpreted as alternative schemes of liquidity (not credit) risk management. The model emphasizes the interdependencies in entrepreneurs’ animal spirits, liquidity risk management schemes adopted by financial institutions, and effective demand of households. The underlying idea is that fluctuations in the composition of property incomes trigger fluctuations in non-financial investment that, in turn, drive fluctuations in spending. The article finds that both relationship and shadow banking must have a pro-cyclical impact, and differences are essentially based on different liquidity risk management aggregate cost functions. The model developed here suggests that securitisation does not per se affect the financial sustainability of the growth process, but regulatory measures aimed at checking predatory lending and re-securitisation activities are needed to avoid possible adverse impacts on animal spirits. JEL codes: E44, G20, O16